2021
DOI: 10.1371/journal.pone.0260053
|View full text |Cite|
|
Sign up to set email alerts
|

Physical activity promotion in an urban district: Analyzing the mechanisms of interorganizational cooperation

Abstract: Past research has identified the importance of cooperation among community-based organizations from different sectors to address public health problems such as insufficient physical activity. However, little is known about how and why interorganizational cooperation occurs. The present study sought to analyze the structure and emergent patterns of interorganizational cooperation within a network promoting physical activity based in an urban district neighborhood of a city in Southwestern Germany. Survey data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…In some studies using SNA, organizations in the same sector cooperate more often with each other, indicating homophily as a mechanism of cooperative tie formation [ 59 , 63 ]. However, other network studies have found that organizations from different sectors are more likely to establish a relationship, indicating heterophily as a mechanism of cooperative tie formation [ 18 , 56 , 60 ]. An effect frequently observed is that cooperation in these networks takes place in triangles [ 18 , 63 ], i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some studies using SNA, organizations in the same sector cooperate more often with each other, indicating homophily as a mechanism of cooperative tie formation [ 59 , 63 ]. However, other network studies have found that organizations from different sectors are more likely to establish a relationship, indicating heterophily as a mechanism of cooperative tie formation [ 18 , 56 , 60 ]. An effect frequently observed is that cooperation in these networks takes place in triangles [ 18 , 63 ], i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on cooperation networks of organizations engaged in sport and PA promotion show rather heterogeneous results [31], both in terms of network characteristics and in terms of the predictors of cooperation. While some networks have a moderate to high density with a variety of realized relationships [56][57][58], other networks are rather fragmented with low levels of cooperation [18,19,59,60]. In some networks, cooperation is characterized by centralization of a few actors that hold by far the highest number of cooperative ties or act as gatekeepers [56,58,60,61], whereas in other networks the relationships between the organizations are evenly distributed and represent a decentralized network [19,59,62].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation